Understanding the Impact of Mesh on Tank Overflow System Capacity. Issue 12 (17th October 2018) - Burkhardt, Jonathan B.; Goodrich, James A.; Szabo, Jeff; Hall, John; Crosby, Jake; Tourney, Seth; Clement, Robert
Abstract : A 2016 incident that resulted in damage to a water storage tank's roof motivated pilot‐scale experiments to be conducted to determine the impact of mesh on tank overflow capacity. A clean mesh installed near the outlet of an overflow system did not reduce the capacity during the weir‐dominated flow regime. Mesh was found to reduce the area available to flow, which was found to lower the achievable capacity through the system. Considering only the head loss or pressure drop associated with the mesh, and not area reduction, resulted in an overestimation of achievable capacity, which could lead to an undersized overflow system. The results and formulas presented will help water utilities ensure that overflow systems with mesh are appropriately sized.